Successful implementation of rituximab in patients with severe refractory forms of granulomatosis with polyangiitis - Bolpačić, Jasna; Savić, Nevena; Aranđelović, Snežana; Tomić-Spirić, Vesna; Rašković, Sanvila; Perić-Popadić, Aleksandra (Vojnosanitetski pregled, 2021)
Abstract Introduction. Wegeners’s granulomatosis is a disease characterized by granulomatous inflammation of the upper and/or lower respiratory tract, glomerulonephritis with varying degrees of small vessel vasculitis and classic anti-neutrophil cytoplasmic antibodies (c-ANCA) findings. The treatment uses different modalities of immunosuppressive therapy which does not always lead to remission. We presented the efficacy of biological therapy in a patient with refractory form of the Wegeners’s granulomatosis. Case report. A 23-years-old patient, was treated in August, 2011 at the Clinic of Otorhinolaryngology and Maxillofacial Surgery of the Clinical Center of Serbia because of suppurative otitis media, resulting twice in mastoidectomy. On the day 7 after the surgery, hemoptysis and fever occurred. Considering lung x-ray that showed presence of the round soft-tissue changes on both sides, nonspecific inflammatory syndrome in laboratory analysis and  positive c-ANCA (1 : 160) with high titers the antibodies to the proteinase 3 (anti-PR 3),  Wegener's granulomatosis was diagnosed. Due to the fact that administration of glucocorticoids, cyclophosphamide and immunomodulatory dose of immunoglobulin did not lead to clinical remission, it was decided to apply rituximab. After its application clinical remission occurred and it lasted fifteen months. Conclusion. Application of biologic therapy might be successful in the treatment of patients with severe form of refractory granulomatosis with polyangiitis.
Keywords: granulomatosis with polyangiitis; therapeutics; biological therapy; rituximab; treatment outcome